The financing of development - challenges and opportunities for CARICOM countries - Insanally, S. R. ([Caribbean Centre for Money and Finance] [St. Augustine]TT, 2009)
Looks at the traditional sources of development financing and makes recommendations for new and additional sources. Highlights CARICOM's position and response as well as the global response. Suggests that we must seek to remove development and the financing of development from the colonial context in which they were conceived.